Prognostic Impact of Oncogenic Fibroblast Growth Factor Receptor Alterations in Patients With Advanced Solid Tumors in a Real‐World Setting - Levon Demirdjian; Spyros Triantos; Kristopher Standish; Shibu Thomas; Qi Xia; Jiarui Zhang; Joel Greshock; Julie Paone; Paige Sheridan; Shubham Pant; Christophe Massard; David A. Reardon; et al. (Cancer Medicine)
ABSTRACT Background Somatic FGFR gene alterations (FGFRalt) may act as oncogenic drivers across several cancers. The prognostic impact of FGFRalt in solid tumors is not fully understood. We assessed the prognostic impact of FGFRalt on overall survival (OS) in a tumor‐agnostic real‐world cohort of patients with advanced solid tumors. Methods This was a retrospective, observational, comparative cohort analysis that used data from a nationwide de‐identified clinico‐genomic database. Patients were included if they had advanced/metastatic disease, were aged ≥ 18 years at the time of diagnosis, had evidence of genomic testing for FGFRalt, and had initiated first‐line systemic therapy for their cancer. Patients without FGFR alterations (FGFRneg) were matched 3:1 with patients with FGFRalt using a combination of exact matching on tumor type and Mahalanobis‐distance matching on selected clinical confounders. The primary endpoint was OS from time of initiation of first‐line therapy in patients with FGFRalt versus FGFRneg. To further mitigate bias, delayed entry models and covariate‐adjusted stratified Cox models were implemented. Results The final cohort included 1012 patients (253 FGFRalt, 759 FGFRneg), across 30 tumor types. There were no significant differences in real‐world OS from first‐line therapy between FGFRalt and FGFRneg groups (hazard ratio 0.97; p = 0.78). Median OS from initiation of first‐line therapy was 1.13 years (95% confidence interval [CI] 0.92–1.52) and 1.01 years (0.89–1.15) for the FGFRalt and FGFRneg groups, respectively. Conclusions In this matched‐cohort real‐world analysis, presence of FGFRalt had no impact on the prognosis of patients with advanced solid tumors receiving standard‐of‐care treatment.